Church Building as a Secular Endeavour: Three Cases from Eastern Germany - Halemba, Agnieszka (Religions, 2023)
Political secularism can be defined as a kind of political philosophy that sees the secular state as setting the terms of encounter between the secular and the religious. However, religion and religious organisations are not necessarily seen as oppositional to the secular state; there can be myriad forms of coexistence between secular and religious authorities. The argument forwarded in this article is based on ethnographic research focussing on the presence and social significance of religious materiality in the region considered to be one of the most secularised worldwide—the north-eastern part of contemporary Germany. I investigate the strategies of actors socially recognised as either religious or secular towards each other, looking at how secular actors assign a place to religious symbols, materiality, theological concepts, organisations, and communities; on the other hand I investigate strategies that religious actors adopt in a context of political secularism. Even if political secularism presupposes supremacy of the secular state over religious actors and the right of the former to make legally binding decisions concerning the latter, those religious actors are not passive—they react to secular initiatives and they try to carve for themselves a space in a public sphere, while at the same time the secular or rather nonreligious actors mobilize religious elements for a variety of reasons.